Holistic Education in Forming Integral Human Beings - Assa’di, Much. Misbah; Benny Kurniawan; Atim Rinawati; Moh. Agus Salim; Ali Mahfud (Mataram University, 2025)
Education is a milestone in developing and advancing a country, superior human resources are born from education. The importance of education has become the state's main stream in providing attention through the budget and so on. Good education not only forms people who are competent in science, but also capable in morals and have social competence. Social skills are very necessary to make life peaceful for one another. This research aims to describe holistic education as a whole and explain the important role of implementing holistic education for society. The research method used by the research is a qualitative research method with a research library approach. Data sources are obtained through primary and secondary data, such as scientific journals or related research results, books, magazines or other sources that provide data answers that researchers need. The results of this researcher are that holistic education leads a person to become a complete person, with a deep understanding of religion, critical thinking skills, good social skills, and maintained physical and emotional health. This education not only emphasizes knowledge, but also the formation of attitudes and values ​​that enable individuals to interact positively with the surrounding environment.